How Individual Factors Shape Innovative Work Behavior in Malaysian HEIs: The Role of Innovation Capability, Knowledge Sharing and Psychological Empowerment - Irzan Ismail; Zarina Begum Ebrahim; Erne Suzila Kassim (Information Management and Business Review, 2024)
This study investigates the factors driving academics' innovative work behavior (IWB) in Malaysian Higher Education Institutions (HEIs), focusing on individual innovation capability, psychological empowerment, and knowledge sharing. The respondents comprised 382 academics from 24 Malaysian universities listed in the QS World Ranking 2023, selected through convenience sampling. Data were collected via a Google Form questionnaire distributed by email. The descriptive analysis assessed individual innovation capabilities, psychological empowerment, and knowledge-sharing levels, and their impact on IWB. The findings indicate high engagement in innovative activities, with academics demonstrating strong innovative capabilities, a sense of empowerment, and active knowledge-sharing practices. These individual factors significantly contribute to fostering IWB, highlighting the importance of continuous professional development, supportive institutional environments, and collaborative cultures in promoting innovation within HEIs. This study provides valuable insights for policymakers and university administrators to enhance the innovative potential of academics, ultimately contributing to the advancement of knowledge and improvement of educational practices in Malaysian HEIs. Future research should explore longitudinal effects and potential moderating factors to further understand innovative work behavior dynamics in academic settings.